Causes of Current Account Fluctuations in West African Monetary Union - Diallo, Amadou Woury (Asian Journal of Economics and Empirical Research, 2020)
This study analyzes the sources of current account fluctuations in the West African Monetary Union (WAEMU) economies over the period from 1980 to 2017. It is part of the inter-temporal approach which considers that the dynamics of the current account of a country is influenced by global shocks and transient or permanent domestic shocks. Thus, we developed a three-variable structural autoregressive vector model. This is the international real interest rate that represents the aggregate shock, the ratio of current account to gross domestic product which is the proxy for transient domestic shocks, and the ratio of net output to gross domestic product to measure impact of permanent shocks to the current account. From the theoretical model, structural shocks are identified by applying the long-term restrictions imposed by the inter-temporal approach in the analysis of current account dynamics. The study leads to three major results: 1) current account fluctuations within WAEMU are explained by transient domestic shocks, 2) net product fluctuations are due to permanent domestic shocks, 3) Global or exogenous shocks have a modest contribution to current account fluctuations, but their effects on net income are still significant, especially in the long run.